CONTENT VALIDITY OF THE MATHEMATICS LEARNING INDEPENDENCE INSTRUMENT FOR JUNIOR HIGH SCHOOL STUDENTS USING AIKEN’S V - Ahmad, Ahmad; Dos Santos, Mariano; Helmiyatun, Helmiyatun; Hidayah, Nurul; Parihin, Parihin (UIR PRESS, 2025)
This study examines the content validity of a mathematics learning independence instrument for junior high school students, developed based on five key dimensions: initiative, discipline, responsibility, time management, and problem solving. The instrument includes 20 items rated by four experts using a 1–5 Likert scale. Aiken's V index was used to measure expert agreement on item relevance. Results showed that 6 items had high validity (V ≥ 0.8125), 13 had moderate validity (0.5 ≤ V < 0.75), and 1 item had low validity (V = 0.375). The highest V score was 0.875, and the lowest was 0.375. These findings indicate that most items are acceptable but may require slight revision to better reflect the intended constructs. The study highlights the importance of expert input and the utility of Aiken’s V in validating instrument content. A valid instrument is essential for accurately assessing student learning independence, especially in junior high school mathematics education.